2021
DOI: 10.1111/1755-6724.14379
|View full text |Cite
|
Sign up to set email alerts
|

Geochemistry and Petrogenesis of Late Ediacaran Rare‐metal Albite Granites of the Arabian‐Nubian Shield

Abstract: The Abu Dabbab albite granite (ADAG), in the central Eastern Desert of Egypt, hosts the most significant rare metal ore deposit in the northern part of the Neoproterozoic Arabian-Nubian Shield. Here, we report detailed field, petrographic, mineralogical and geochemical investigation of the ADAG, an isolated stock-like granitic body with sharp intrusive contacts against metamorphic country rocks, probably emplaced at about 600 Ma. The fine-grained porphyritic upper unit is a preserved remnant of the shallowly-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 107 publications
(138 reference statements)
5
16
0
Order By: Relevance
“…5f), their high Mn contents place them outside the S-type magmatic field of Dahlquist et al (2007) and outside any of the granite-type garnet fields in the compilation of Zhang et al (2012). Yet the compositions of the garnets from the present study are similar to garnet compositions reported from several post-collisional granites in the Eastern Desert of Egypt (Azer et al, 2019;Abuamarah et al, 2019). The most likely resolution of the observation that the garnet compositions in the Mueilha garnet-bearing phase are broadly magmatic and yet anomalous compared to all the standard tectonicallyinterpreted granite types is that they represent a transitional stage, somewhere on the spectrum from late-magmatic to hydrothermal, having grown from a very H 2 O-and Frich silica-rich peralkaline magma at a temperature below the F-free granite minimum.…”
Section: Evidence For Magmatic Vs Metasomatic Effectssupporting
confidence: 79%
See 4 more Smart Citations
“…5f), their high Mn contents place them outside the S-type magmatic field of Dahlquist et al (2007) and outside any of the granite-type garnet fields in the compilation of Zhang et al (2012). Yet the compositions of the garnets from the present study are similar to garnet compositions reported from several post-collisional granites in the Eastern Desert of Egypt (Azer et al, 2019;Abuamarah et al, 2019). The most likely resolution of the observation that the garnet compositions in the Mueilha garnet-bearing phase are broadly magmatic and yet anomalous compared to all the standard tectonicallyinterpreted granite types is that they represent a transitional stage, somewhere on the spectrum from late-magmatic to hydrothermal, having grown from a very H 2 O-and Frich silica-rich peralkaline magma at a temperature below the F-free granite minimum.…”
Section: Evidence For Magmatic Vs Metasomatic Effectssupporting
confidence: 79%
“…The concentrations are well-correlated with SiO 2 for most elements. Similar variability has been described in other rare-metal bearing granites in the Eastern Desert of Egypt (Abuamarah et al, 2019;Azer et al, 2019;Heikal et al, 2019). Selected trace elements are plotted against SiO 2 in Fig.…”
Section: Geochemical Characteristicssupporting
confidence: 78%
See 3 more Smart Citations